2021
DOI: 10.3390/molecules26237220
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Herbaceous and Woody Cell Wall Digestibility by Pathogenic Fungi

Abstract: Fungal pathogens have evolved combinations of plant cell-wall-degrading enzymes (PCWDEs) to deconstruct host plant cell walls (PCWs). An understanding of this process is hoped to create a basis for improving plant biomass conversion efficiency into sustainable biofuels and bioproducts. Here, an approach integrating enzyme activity assay, biomass pretreatment, field emission scanning electron microscopy (FESEM), and genomic analysis of PCWDEs were applied to examine digestibility or degradability of selected wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
1
0
0
Order By: Relevance
“…In the generated PAW, short-living active oxygen and nitrogen species such as hydroxyl- (·OH), nitric oxide- (NO _ ), superoxide (·O 2 − ) radicals, and ozone (O 3 ) are formed, and further react yielding nitric oxide (NO), nitrate (NO 3 − ) and nitrite (NO 2 − ), peroxynitrite (ONOO − ), and hydrogen peroxide (H 2 O 2 ) [ 10 , 11 ]. These reports confirmed that PAW can stimulate plant growth [ 12 ] and control diseases [ 13 ]. However, weekly foliar PAW treatments did not have a significant effect on the accumulation of corn biomass, or on foliar nutrient content [ 14 ].…”
Section: Introductionsupporting
confidence: 63%
“…In the generated PAW, short-living active oxygen and nitrogen species such as hydroxyl- (·OH), nitric oxide- (NO _ ), superoxide (·O 2 − ) radicals, and ozone (O 3 ) are formed, and further react yielding nitric oxide (NO), nitrate (NO 3 − ) and nitrite (NO 2 − ), peroxynitrite (ONOO − ), and hydrogen peroxide (H 2 O 2 ) [ 10 , 11 ]. These reports confirmed that PAW can stimulate plant growth [ 12 ] and control diseases [ 13 ]. However, weekly foliar PAW treatments did not have a significant effect on the accumulation of corn biomass, or on foliar nutrient content [ 14 ].…”
Section: Introductionsupporting
confidence: 63%